Mini Glass Ceilings and Queen Bees in Management of South African Organisations - Du Preez, Samantha (University of the Witwatersrand, Johannesburg, 2024)
Gender equality in the workplace remains a business and Government imperative. Although the South African transformation journey had a positive impact to female careers by way of affirmative action policy, female career advancement remains lethargic. This study delves into the complex challenges hindering female career advancement, focusing on two prominent phenomena: the glass ceiling and queen bee syndrome. The glass ceiling refers to invisible yet formidable barriers that prevent women from ascending to leadership positions within organizations. It encompasses systemic biases, gender stereotyping, and organisational culture discrimination against females, creating a tangible, albeit invisible barrier to women's professional growth. Conversely, the queen bee syndrome describes a phenomenon where senior women have successfully broken through the glass ceiling, but seemingly creates a toxic barrier which inhibit the progress of their junior female counterparts. In combination, these barriers often perpetuate a hostile and toxic work environment underpinned by competition and lack of support. This quantitative study’s aim was to identify and analyse the prevalence of these barriers in South African organisations today. The study’s findings indicate that both these phenomena are found in the organisations respondents are employed by, with an indication of positive organisational cultures within these workplaces. Recommendations are proposed encompassing organisational intervention with suitable and targeted initiatives to create awareness, educate and guide all managers in the managerial hierarchy.
A research Report presented in fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand Johannesburg 2024
Keywords: Glass ceiling; Queen Bees; Management; South African organisations; UCTD; SDG-8: Decent work and economic growth